Long term agroecosystem research experimental watershed network. Issue 3 (20th March 2022) - Goodrich, David C.; Bosch, David; Bryant, Ray; Cosh, Mike H.; Endale, Dinku; Veith, Tamie; Kleinman, Peter; Langendoen, Eddy; McCarty, Greg; Pierson, Fred; Schomberg, Harry; Smith, Douglas; et al.
Abstract: The vision of the Long Term Agroecosystem Research (LTAR) network is to enable multi‐decadal, trans‐disciplinary, and cross‐location science to ensure the long‐term sustainability of U.S. agriculture. LTAR's primary goals are to: (1) Intensify agricultural productivity, (2) Improve ecosystem services related to agricultural production, and (3) Improve rural prosperity. The LTAR network includes 18 locations (sites). It includes 10 existing hydrologic observatories from the Agricultural Research Service‐Experimental Watershed Network (ARS‐EWN) that were established before the creation of LTAR. Background and an overview of the network are presented.